Antarctic snow vehicle - Masayuki Hosoya (Antarctic Record, 1985)
This paper describes the characteristics of the antarctic snow vehicle, domestic market of the snow vehicle, changes and the present situation of the snow vehicle after the establishment of the antarctic station and some problems of the antarctic snow vehicle. Japanese Antarctic Research Expedition is presently equipped with three types of snow vehicle, SM50S, SM40S and SM20S. These snow vehicles are used in the inland trips and sea ice exploring, in transportation of cargo to inland station, as well as to Syowa Station and its outskirts.